2008
DOI: 10.1158/0008-5472.can-07-6710
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Copy Number Analysis in Esophageal Adenocarcinoma Using High-Density Single-Nucleotide Polymorphism Arrays

Abstract: We applied whole-genome single-nucleotide polymorphism arrays to define a comprehensive genetic profile of 23 esophageal adenocarcinoma (EAC) primary tumor biopsies based on loss of heterozygosity (LOH) and DNA copy number changes. Alterations were common, averaging 97 (range, 23-208) per tumor. LOH and gains averaged 33 (range, 3-83) and 31 (range, 11-73) per tumor, respectively. Copy neutral LOH events averaged 27 (range, 7-57) per EAC. We noted 126 homozygous deletions (HD) across the EAC panel (range, 0-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 39 publications
11
83
1
Order By: Relevance
“…(177) (195) (Continued on the following page) decade, several studies conducted using advanced genomic techniques such as array-comparative genomic hybridization (aCGH) and SNP arrays confirmed previously reported copy number alterations and identified novel genomic loci undergoing changes during process of metaplasia-dysplasia-carcinoma development (54)(55)(56)(57)(58)(59)(60). It has been shown that as the disease progresses from early to late stages, SNP abnormalities increase from approximately 2% to 30% (54,57).…”
Section: Genomic Instabilitymentioning
confidence: 76%
See 1 more Smart Citation
“…(177) (195) (Continued on the following page) decade, several studies conducted using advanced genomic techniques such as array-comparative genomic hybridization (aCGH) and SNP arrays confirmed previously reported copy number alterations and identified novel genomic loci undergoing changes during process of metaplasia-dysplasia-carcinoma development (54)(55)(56)(57)(58)(59)(60). It has been shown that as the disease progresses from early to late stages, SNP abnormalities increase from approximately 2% to 30% (54,57).…”
Section: Genomic Instabilitymentioning
confidence: 76%
“…It has been shown that as the disease progresses from early to late stages, SNP abnormalities increase from approximately 2% to 30% (54,57). The total number of SNP alterations in tissue samples is tightly correlated with previously reported DNA abnormalities such as aneuploidy, copy number alterations, and LOH highlighting the application of SNP-based genotyping to assess genomic abnormalities (54)(55)(56)(57)(58)(59)(60). Thus, SNP-based genotyping provides an alternative way to assess genomic abnormalities during EAC pathogenesis.…”
Section: Genomic Instabilitymentioning
confidence: 96%
“…Copy number information was obtained from the dataset by Nancarrow et al 14 (GEO accession number GSE 10506). This is the only aCGH dataset currently publicly available with patient survival information.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12] There is considerable evidence that chromosomal instability plays a role in the progression of BE to EAC, including both gains and losses of whole chromosomes or parts of chromosomes. [13][14][15] Molecular studies of BE epithelia led to the discovery that 9p LOH and CDKN2A negative. CIMP status has been shown to correlate with particular genetic mutations (e.g., CIMP-high cancers with BRAF mutations) as well as clinical parameters (e.g., CIMP-high cancers are more common in female patients and are frequently located in the right colon).…”
Section: Dna Methylation Profiling In Barrett's Esophagus and Esophagmentioning
confidence: 99%